Complementing the Scholarship of Teaching and Learning with Engaged Pedagogy and Community Cultural Wealth - Rolf Straubhaar (InSight)
For Students of Color in the United States, to attend university is to live and work within a social reality that reproduces a hegemonic social order. Professors can and should assist students in recognizing the dominant social standpoint embodied in much of university instruction, while also recognizing the equal validity of their own and their students’ socially situated standpoints. Building upon the scholarship of teaching and learning, I here present two pedagogical frameworks that have been constructed to recognize particular standpoints and work from them towards justice: bell hooks’ engaged pedagogy and Yosso and Solórzano’s community cultural wealth model. I also present practical applications of both, drawing on my own university teaching experience.